Social and regional inequalities in the sense of safety in Germany - Anna Bindler; Hannah Walther (DIW Weekly Report, 2025)
The public's perceived sense of safety influences many domains in significant ways: It impacts individual behavior, life quality, consumption behavior, and even political views as well as government action. Using data from the Socio-Economic Panel (SOEP) and the German Federal Government's 2024 Gleichwertigkeitsbericht (Equivalence Report), the development as well as the regional and social distribution of the sense of safety in Germany is analyzed. The results make it clear that not only does the fear of crime correlate with actual crime rates, but it can even increase independently of them. Such an increase can be seen during times of social upheaval. Regionally, there is a clear north-south divide: There is less crime in the south and people who live there feel safer than people living in the north. The fear of crime is distributed unevenly across society, particularly among vulnerable groups. People with a migration background tend to feel less safe. Young people, men, people with a university degree, or high-income earners are less concerned about crime trends. Responsible media coverage and a rational public discourse are important in order to prevent a growing gap between the public's subjective perception of crime and the objective crime situation. Policymakers and the media should focus on informing the public rather than amplifying fears.
Keywords: K42; K14; R19; J10; 330; crime; crime perceptions; public security; regional inequality; social inequality